Liver Protective Assessment of Garlic Oil in the Presence of Alcohol - Aliasghar Keramatinia; Reza Robati; Zahra Razzagh; Babak Arjmand; Amirali Aghamohammadi; Fatemeh Bandarian; Farideh Razi; Mostafa Rezaei Tavirani*; Mohammad Rostami Nejad (Iranian Society of Pharmacognosy, 2024)
Background and objectives: There is evidence that alcohol consumption is associated with liver damage. The positive role of garlic in preventing liver versus alcohol-related liver disease has been investigated before. In the present study, the possible protective role of garlic oil on the liver versus alcohol was evaluated via protein-protein interaction (PPI) network analysis to provide a new perspective of molecular events. Methods: GSE40334 from the Gene Expression Omnibus (GEO) database was selected for analysis. The significant differential expressed genes (DEGs) were determined by using the GEO2R program. UMAP analysis was applied to explore the separation of samples by analysis. Action map and gene ontology were used via Cytoscape software v 3.7.2 and its applications to find the critical DEGs and biological processes. Results: A number 798 significant DEGs were selected for analysis. The PPI network analysis showed that two clusters of DEGs play significant roles in response to garlic oil.  Ranbp2, Pafah1b1, Seh1l, Plk1, Cenpa, Mis12, and Tgfb1 as the crucial DEGs were highlighted. The biological processes related to the essential function of cells such as proliferation and cell division were identified as the regulated biological terms. Conclusion: Garlic oil plays a protective role in preventing liver damage versus consuming alcohol. Among seven crucial genes, six individuals were regulated to enhance liver health.